Analisis Efisiensi Operasional BMT UGT Sidogiri Sebelum dan Sesudah Implementasi Aplikasi Mobile UGT: Studi Kasus capem Gadang - Suhaimah, Suhaimah; Maulida, Nabila Adenina Zidni (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze efforts to improve operational efficiency at BMT UGT Sidogiri through the use of the Mobile UGT application. The background of this study is the need for digital transformation to accelerate the service process and improve operational quality, especially in Capem Gadang. The method used is qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation studies of 10 informants consisting of staff and members of BMT UGT Sidogiri. The focus of the study is Capem Gadang. The results of the study indicate that the use of the Mobile UGT application significantly facilitates the transaction process, accelerates services, and improves the accuracy of administrative and financial data. This application also expands the reach of services and increases member satisfaction without causing significant operational constraints. In practice, this study recommends the adoption of digital technology through the Mobile UGT application as an effective strategy in improving operational efficiency and encouraging the growth of technology-based sharia financial services at BMT UGT Sidogiri. In conclusion, the presence of the Mobile UGT application has been proven to be able to improve operational efficiency while providing a positive impact on the development of technology-based sharia financial services